2012
DOI: 10.1371/journal.pone.0036762
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Chemotherapy Leads to the Selection of ABCB5-Expressing Cells

Abstract: Metastatic melanoma is the most aggressive skin cancer. Recently, phenotypically distinct subpopulations of tumor cells were identified. Among them, ABCB5-expressing cells were proposed to display an enhanced tumorigenicity with stem cell-like properties. In addition, ABCB5+ cells are thought to participate to chemoresistance through a potential efflux function of ABCB5. Nevertheless, the fate of these cells upon drugs that are used in melanoma chemotherapy remains to be clarified. Here we explored the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 33 publications
4
85
0
4
Order By: Relevance
“…As expected for melanoma SCs, live GFP high cells overexpressed ABCB5 and CD271 surface markers, conferring their CSC phenotype [19,20,30], and consistently, TNF significantly (p < 0.01) increased the pool of GFP high-…”
Section: Pro-inflammatory Tnf Increases the Proportion Of Label-retaisupporting
confidence: 69%
“…As expected for melanoma SCs, live GFP high cells overexpressed ABCB5 and CD271 surface markers, conferring their CSC phenotype [19,20,30], and consistently, TNF significantly (p < 0.01) increased the pool of GFP high-…”
Section: Pro-inflammatory Tnf Increases the Proportion Of Label-retaisupporting
confidence: 69%
“…Furthermore, the proportion of CD133-positive cells in U251 glioma cells increases after the administration of rotenone and ethidium bromide [182]. Recent research has revealed that melanoma cells are enriched in ABCB5-expressing cells after temozolomide treatment and that these ABCB5-expressing cells exhibit enhanced tumorigenicity, with SC-like properties [183]. Ionizing radiation can activate stemness pathways in HCC cells and can result in the enrichment of a CSC subpopulation with higher resistance to radiotherapy [184].…”
Section: Cytotoxic and Hypoxic Resistancementioning
confidence: 99%
“…Besides their ability to differentiate into various cell types [9], MSCs have the ability to form "melanoma spheroids" when grown in serum-free medium supplemented with growth factors [10], and exhibit self-renewal activity in vitro [1,11] and tumorigenic potency in vivo [12]. MSCs are also characterized by the expression of stem cell markers including CD20, CD133 [1,9,13], ABCB5 [14], CD166 [1,7], CD146 [15], and Nestin [16]. Also, the elevated expression of Bmi-1 has been reported in MSCs [17].…”
Section: Introductionmentioning
confidence: 99%